2008
DOI: 10.1055/s-2007-1019628
|View full text |Cite
|
Sign up to set email alerts
|

Course of the Manic-Depressive Cycle and Changes Caused by Treatments

Abstract: The course of 434 bipolar patients (256 women, 178 men) was studied longitudinally. The prevailing patterns of the manic-depressive cycles at the end of the observation time were: mania followed by depression (usually mild), 28%; depression followed by mania (usually hypomania), 25%; and continuous circular course, with long cycles, 19%, or with short (rapid) cycles, 20%. The cycles followed an irregular pattern in 8% of the patients.As to the intensity of the episodes, 52% of the patients had severe depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
105
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(130 citation statements)
references
References 8 publications
13
105
0
3
Order By: Relevance
“…Koukopoulos et al (1980) investigating the different patterns of manic depressive cycles, observed that 170 out of 434 bipolar patients (39%) had a course that did not include free intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Koukopoulos et al (1980) investigating the different patterns of manic depressive cycles, observed that 170 out of 434 bipolar patients (39%) had a course that did not include free intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports of a possible link between this effect of antidepressants and the induction of a rapid cycling course of bipolar disorders were made by Kukopulos et al [26] and Wehr et al [27] . The term rapid-cycling bipolar disorder was coined by Dunner et al [28] in 1974 to identify lithium non-responders (further research has confirmed that rapid cycling is a factor of poor prognosis).…”
Section: Of Bipolar Disordermentioning
confidence: 99%
“…These responses may reveal an unrecognized bipolar illness or may be drug induced, since they may also occur in allegedly unipolar patients. In the early 1980s, Kukopulos et al [29] observed how treatment with AD may contribute to changes in the course from unipolar to bipolar illness. They deserve credit for having raised the issue that AD-induced mania may not simply be a temporary and fully reversible phenomenon but may trigger complex biochemical mechanisms of illness deterioration.…”
Section: Tolerance and Its Different Expressionsmentioning
confidence: 99%